2011
DOI: 10.1111/j.1540-4560.2011.01717.x
|View full text |Cite
|
Sign up to set email alerts
|

Matching by Race and Gender in Mentoring Relationships: Keeping our Eyes on the Prize

Abstract: This study examined the extent to which science, technology, engineering, and math (STEM) students reported having had mentors of their own race and gender and the extent to which they have adopted the idea that matching by race and gender matters. The study also documented the effects of race and gender matching on three academic outcomes, self-reported grade point average, efficacy, and confidence, based on data collected from 1,013 undergraduate and graduate students and postdoctoral scholars actively parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
226
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(257 citation statements)
references
References 47 publications
4
226
1
4
Order By: Relevance
“…Students, particularly students of color and women, valued having a mentor of the same race or gender (Blake-Beard, Bayne, Crosby, & Muller, 2011). To succeed in primarily White higher education institutions, faculty must provide African American male students with adequate validation and support (Wood & Palmer, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students, particularly students of color and women, valued having a mentor of the same race or gender (Blake-Beard, Bayne, Crosby, & Muller, 2011). To succeed in primarily White higher education institutions, faculty must provide African American male students with adequate validation and support (Wood & Palmer, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This concept, called "racial/ethnic matching" has been studied in the workplace in general; 53 it has also been studied in specific professions, such as teaching and counseling. 54 Participants indicated that their interaction with users from a similar ethnic background was different from their interaction with users from dissimilar backgrounds.…”
Section: Further Researchmentioning
confidence: 99%
“…The literature reviewed by Cole and Griffin 42 suggests that race does appear to be a notable factor in students' selection of mentors. Similarly, Ong and Wright 38 argue that matched mentors are especially important to women of color, and work by Blake-Beard et al shows that the matching of both race and gender in mentoring relations is particularly important to women of color 46 . However, authors like Ellington and Frederick 47 and JustinJohnson 48 found that women of color often seek mentors outside of their gender and racial group in order to adjust to the culture of their discipline.…”
Section: Mentoringmentioning
confidence: 99%